Teachers and Quality of Learning in Madrasah - Adyaputri, Elvira; Surawan, Surawan; Arsiyah, Arsiyah (Proceeding International Conference on Religion, Science and Education, 2025)
Education must be planned properly and optimally so that the results obtained are also maximum, East Kotawaringin State Madrasah Aliyah (MAN) is the only State Aliyah Madrasah in East Kotawaringin Regency and has been accredited A. This school can be said to be a high school plus religion because its subjects and majors are the same as the subjects and majors in high school in generally. However, the religious lessons are more detailed and deeper. This study aims to describe how the efforts of teachers in improving the quality of learning for students of East Kotawaringin MAN. This research was explored with a qualitative approach. The research subjects were 3 teachers in the field of religious specialization, namely ushul fiqh, Arabic, and the science of interpretation & science of hadith. The research informants were the principal and 77 students of class X majoring in religion. Research data was collected and explored through interviews and documentation techniques. While the results obtained are that the teacher makes various efforts to improve the quality of learning, including: 1) holding a game of throwing questions between students, using the discussion method, dividing into groups to make papers and presenting them, looking attractive and polite. 2) using discussion and practice methods, asking HOTS questions, and preparing several issues (LKS) in the form of online discussion sheets and asking critical questions. 3) using the discussion method, using the Al-Qur'an media and books on hadith science, building good communication, always involving students, understanding every student's behaviour and always providing support.